Analisis Kualitas Situs Web Pemerintah Daerah Pelayanan Perijinan Terpadu terhadap Kepuasan Pengguna Menggunakan Model E-Govqual (Studi Kasus: Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Kutai Barat, Kalimantan Timur) - Anggi Dewi Eka Pratiwi; Niken Hendrakusma Wardani; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Penanaman Modal and Pelayanan Terpadu Satu Pintu (DPM-PTSP) become one government agency that has implemented e-gov in its services. One of the services provided by the One Stop Investment and Integrated Services Office is the Integrated Licensing website (http://www.perijinan.kubarkab.go.id). This study aims to determine the quality of Integrated Licensing website services to user satisfaction. The variables studied were adjusted to the e-govqual model consisting of Usability, Information Quality, Security, Public Responsiveness. The type of data obtained in this study is in the form of qualitative data. Data collection was carried out by interviewing 6 participants, which were divided into two categories namely, participants who had used it and those who had never used it. The results obtained from this study, the Usability variable was considered good, but the Multilingual indicator was not yet available. Information Quality is considered quite good, the Information Timeliness indicator, the timeliness of displaying information needs to be improved. The Security variable gets a good rating but still needs to improve the security of the user's data privacy on the website or through agencies. Public Responsiveness variable is considered quite good. In the Government Responsiveness indicator it is necessary to improve the response to responses to questions and questions from citizens of users.